Philosophical Foundations of Ethics in Medical Sciences with Islamic Approach - Hossein Mahmoodian (Shiraz University of Medical Sciences, 2021)
Introduction: Any area of human knowledge is based on special philosophical foundations. These foundations determine the basic framework and paradigm of the area. Ontology, epistemology, methodology, and anthropology are the philosophical foundations that form a specific knowledge area. Ethics in medical sciences has its own philosophical foundations in Islamic framework. Using Islamic texts in general and the holy Quran in particular, this research/study attempts to analyze and identify these foundations, and, in an attempt to execute a part of the objectives of the Comprehensive and Scientific Map of Iran, it tries to localize and Islamicize these foundations.   Methods: This is a qualitative research that is based on emergent design. The data collection procedure is documentary and library resource and the data analysis approach is considered to be descriptive-interpretive. Islamic texts and the holy Quran in particular are sources of extraction of our intended components and criteria. Results: According to the foundations of Ontology, Epistemology, Methodology, and Islamic Anthropology, the most important characteristics of ethics in medical sciences include monotheism, motivations for closeness to God, kindness, and virtue. Other practical concepts such as thralldomand purification of soul are also taken into account in this study. Conclusion: Using the capacity of Islamic moral education system, doctors and other healthcare providers could achieve Islamic and humanity goals in medical sciences. The medical education system of universities of medical sciences can use philosophical principles of Islamic ethical system in their curriculum programs and internships as a basis to improve students’ attitude, motivation and skills based on Islamic foundations.